PERAN KELOMPOK TANI AKASIA TERHADAP KEBERDAYAAN PETANI PADI SAWAH DI DESA CABEAN KECAMATAN DEMAK KABUPATEN DEMAK JAWA TENGAH - Latifarruhma, Ella; Dalmiyatun, Tutik; Mardiningsih, Dyah (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
Indonesia is an agricultural country where the majority of population has a livelihood as a farmers. Rice is one of the many agricultural commodities needed by the community to fulfill their daily needs. Rice farmers has problems running their farms so they join a group to solve the problem. Farmers group have a role as a learning class, a vehicle for cooperation, production units and business units, sampling is done using census method, the data taken is primary data and secondary data which is then analyzed using simple regression. The result of the study show that farmer group as a learning class has a high category, as vehicle of cooperation has a moderate category, as a production units has a moderate category and as a business units has a high category. Akasia farmer groups have taken on all the roles as a farmer groups. Advice given is the existence of a rice storage warehouse facility for members of the akasia farmer groups.